Hurray for Fermat and Wiles!: A Bibliographic Essay on the Modern Literature Pertaining to Arguably the World's Most Famous Unsolved (until May 1995) Mathematical Theorem. - Glenn Masuchika (Issues in Science and Technology Librarianship)
In May 1995, the major mathematical journal Annals of Mathematics published two articles together proving Fermat's Last Theorem, a mathematical problem that has frustrated mathematicians for over 350 years. This article will cover the short modern bibliographic record leading to its solution. [ABSTRACT FROM AUTHOR]